The Influence of Internal Communication On Employee Productivity At The Axana Hotel Padang - Arda, Arda Dian Nugraha; Azmen Kahar (Journal of Multidimensional Management, 2025)
This study aims to analyze the effect of internal communication on employee productivity at The Axana Hotel Padang. The research employs an associative quantitative approach with a population of 61 employees, using a total sampling technique. Data were collected through a Likert-scale questionnaire that had been tested for validity and reliability. The results of multiple linear regression analysis show that internal communication (regression coefficient = 0.401; t = 3.892; p = 0.000) has a positive and significant effect on employee productivity. Path analysis indicates that the direct influence of internal communication on employee productivity is 0.605, while the indirect effect through other variables is 0.088, resulting in a total effect of 0.693. These findings demonstrate that effective internal communication can significantly enhance employee productivity. The results of this research are expected to serve as a reference for hotel management in formulating more effective and productive human resource policies